Fixed wireless routes for Internet access. - Dutta-Roy, A.
The author discusses the use of fixed radio access in urban and rural locations for Internet access. The costs involved are discussed and compared to wired access costs. The frequency bands available are considered as are the propagation conditions and antenna aspects
Keywords: Internet access; Antenna aspects; Costs; Fixed radio access; Fixed wireless routes; Frequency band; Propagation conditions; Rural locations; Urban locations